LEIOMYOMA URINARY BLADDER, MIMICKING UROTHELIAL CANCER - Bangash, Muhibullah; Faruqui, Nuzhat; Muhammad , Anis-ul-Islam; Uddin, Zeeshan (Journal of Ayub Medical College Abbottabad, 2021)
Leiomyoma of the urinary bladder is a rare bladder tumour, which is benign in nature. On presentation, it resembles urothelial cancer but it has an excellent prognosis. We reported two cases of urinary bladder leiomyoma. Both the patients presented with lower urinary tract symptoms (LUTS) and the patient in the second case also had painless haematuria. Bladder mass was detected initially on ultrasound and confirmed on contrast-enhanced computed tomography (CT). Transurethral resection of bladder tumour was performed in both cases and no recurrence was found on initial follow-up. But the second case had haematuria and recurrence on subsequent follow-up and managed by performing a partial cystectomy. Endoscopic management of bladder leiomyoma is a safe treatment option for bladder leiomyoma and if multiple recurrences noted with symptoms, then partial cystectomy can be considered. Histopathology is the only definitive way of establishing the diagnosis. These patients can be followed up initially with cystoscopy, and if no recurrence is detected, subsequent follow-up can be carried out with ultrasound.